Preparation method and application of copper ferrocyanide / molybdenum disulfide / graphene oxide photo-thermal aerogel
By designing copper ferrocyanide/molybdenum disulfide/graphene oxide photothermal aerogel, combined with its photothermal and photocatalytic properties, the problems of insufficient water purification evaporation rate and pollutant removal efficiency in the prior art are solved, and efficient water purification and pollutant degradation are achieved.
Patent Information
- Application Number
- CN202411908966.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, when using graphene aerogel for water purification, the evaporation rate and pollutant removal efficiency are insufficient, and materials such as copper ferrocyanide have difficulties in separation and recycling in practical applications.
By adjusting the structural composition of graphene aerogel, copper ferrocyanide/molybdenum disulfide/graphene oxide photothermal aerogel is designed and prepared. The photothermal and photocatalytic properties of copper ferrocyanide are used, and the photocatalytic capabilities of molybdenum disulfide are combined to improve the evaporation rate of water and pollutant degradation efficiency.
It realizes efficient water quality purification, improves the evaporation rate and pollutant degradation rate, solves the recycling problem of materials in actual applications, and enhances the ability to deal with semi-volatile organic pollutants.
Smart Images

Figure CN119528178A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials and energy-saving and environmental protection technology, and specifically relates to a preparation method and application of copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel. Background Art
[0002] Global water resources are becoming increasingly scarce. Using abundant seawater resources to prepare fresh water and obtaining clean water from polluted water sources are both effective solutions. Solar interfacial distillation is a new technology that combines solar thermal energy utilization and interfacial distillation process to purify seawater, desalinated water and sewage. Its distillation efficiency mainly depends on the selection of interfacial photothermal materials, because photothermal materials can effectively convert solar energy into evaporative heat energy. However, most current research focuses on improving the evaporation rate of water and the utilization efficiency of solar energy, which may be ineffective in degrading and removing organic pollutants in water. Non-volatile impurities may remain or be enriched in the residual water, which may lead to more serious wastewater pollution. Therefore, it is crucial to develop dual-functional materials that can simultaneously achieve water desalination and catalytic degradation of organic pollutants, including photothermal conversion and catalytic degradation.
[0003] As a carbon-based material, graphene aerogel has a high specific surface area and good thermal conductivity. It can effectively absorb and convert light energy into heat energy, and quickly conduct the absorbed heat to improve the photothermal conversion efficiency. At the same time, it can be effectively separated and recycled. It has become an excellent matrix material for evaporators. However, the evaporation rate and pollutant removal of graphene aerogel as a water purification evaporator are still insufficient, which limits its practicality to a certain extent. Molybdenum disulfide, as an excellent photocatalytic semiconductor material, can effectively generate electron-hole pairs under light conditions and promote the degradation of organic pollutants. This feature can significantly enhance the water purification effect, but its subsequent recycling is relatively difficult. Copper ferrocyanide, as a new functional material, has a simple synthesis method and is economical. With its photothermal and photocatalytic properties, as well as its catalytic effect in the Fenton reaction, it has become an important material for improving water purification and pollutant removal efficiency, but there are separation and recycling problems in practical applications. Summary of the invention
[0004] Based on the technical problems pointed out in the background technology, the present invention aims to provide a method for preparing copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel and its application. By adjusting the aerogel structure composition of graphene, copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel is designed and synthesized, the evaporation rate of water and the utilization efficiency of solar energy are further improved, the catalytic degradation effect in the light-Fenton system is fully exerted, and the degradation of organic pollutants in water is promoted, thereby improving the overall water purification efficiency. The design of this composite aerogel not only improves the photocatalytic performance of the aerogel, but also enhances its ability to handle semi-volatile organic pollutants, so that it shows better effects in water purification processes such as distillation, and finally achieves efficient water purification and environmental governance. Through this innovative material design and application strategy, the characteristics of aerogel can be better utilized, providing an effective solution for water pollution prevention and control, and opening up new ways to address global water shortages and pollution problems.
[0005] The first object of the present invention is to provide a copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel, which is used for solar interfacial distillation to purify water while degrading evaporated semi-volatile organic pollutants to further improve the purity of clean water.
[0006] The copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel provided by the present invention is obtained by growing copper ferrocyanide on the surface of molybdenum disulfide / graphene oxide aerogel.
[0007] Wherein, the aerogel material is polyacrylic acid, and the mass ratio of graphene oxide to molybdenum disulfide is 3-4:1.
[0008] The second object of the present invention is to provide a method for preparing the above-mentioned copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel.
[0009] The present invention provides a method for preparing copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel, comprising the following steps: S1, mixing a graphene oxide dispersion and a molybdenum disulfide dispersion, ultrasonically treating the mixture, adding hydrogen peroxide and a polyacrylic acid aqueous solution, and then hydrothermally reacting the mixture, after the reaction is completed, freeze-drying the product to obtain a molybdenum disulfide / graphene oxide aerogel; S2. growing copper ferrocyanide on the surface of molybdenum disulfide / graphene oxide aerogel, and freeze-drying to obtain copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
[0010] The above-mentioned method for preparing copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel, wherein the concentration of the graphene oxide dispersion described in step S1 is 4~5 mg / mL; the concentration of the molybdenum disulfide dispersion is 1~2 mg / mL; the mass fraction of the hydrogen peroxide solution is 20%~30%; and the concentration of the polyacrylic acid aqueous solution is 1~2 mg / mL.
[0011] Furthermore, the volume ratio of the graphene oxide dispersion, the molybdenum disulfide dispersion, the hydrogen peroxide solution and the polyacrylic acid aqueous solution is 8-10:10-12:3-5:1-2.
[0012] Furthermore, the graphene oxide dispersion is synthesized by a modified Hummers method, and the specific operation is as follows: Under ice bath conditions, 98% concentrated sulfuric acid, graphite powder, sodium nitrate and potassium permanganate were stirred for 1~2 h, heated to 35~40 ℃ and continued to stir for 1~2 h; then heated to 90 ℃, and deionized water was slowly added at 1.8~2 times the volume of concentrated sulfuric acid, and continued to stir for 0.5~1 h; deionized water and hydrogen peroxide were added to terminate the reaction, washed to neutrality, deionized water was used to adjust the concentration of graphene oxide, and dispersed evenly to obtain a graphene oxide dispersion. Among them, the ratio of graphite powder, sodium nitrate and potassium permanganate to concentrated sulfuric acid is: 0.5~1.0 g: 0.5~1.0 g: 3.0~6.0 g: 20~25 mL.
[0013] Furthermore, the preparation method of molybdenum disulfide is as follows: ammonium molybdate tetrahydrate and thiourea are dissolved in deionized water, stirred evenly, reacted at 200-230°C for 24 h, cooled to room temperature after the reaction, washed, and dried to obtain molybdenum disulfide nanosheets.
[0014] Furthermore, the temperature of the hydrothermal reaction in step S1 is 180-200°C, the reaction time is 8 h, and the freeze-drying temperature is -50--60°C, and the time is 48-72 h.
[0015] The preparation method of the above-mentioned copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel, wherein the specific operation of step S2 is: placing the molybdenum disulfide / graphene oxide aerogel in a cupric chloride solution for reaction for 2 h, then transferring it to a potassium ferrocyanide solution for reaction for 4 h, then washing it with deionized water 2 to 3 times, and freeze-drying it to allow copper ferrocyanide to grow on the surface of the molybdenum disulfide / graphene oxide aerogel.
[0016] Further, step S2 is repeated multiple times to obtain copper ferrocyanide-modified molybdenum disulfide / graphene oxide aerogel.
[0017] Furthermore, the concentration of the cupric chloride solution is 0.03-0.5 mol / L, preferably 0.1-0.3 mol / L, and the concentration of the potassium ferrocyanide solution is 0.03-0.5 mol / L, preferably 0.1-0.3 mol / L.
[0018] Furthermore, in step S2, the freeze-drying temperature is -50°C and the time is 72 h.
[0019] The third object of the present invention is to provide an application of copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel.
[0020] Specifically, the photothermal aerogel is used for seawater desalination and semi-volatile organic compounds (SVOCs) wastewater purification by solar-driven interfacial evaporation.
[0021] Furthermore, the semi-volatile organic compound is nitrobenzene.
[0022] In summary, the present invention has the following beneficial effects: (1) The three-dimensional network structure of the aerogel retains the properties of graphene oxide with high specific surface area and good mechanical properties. The introduction of molybdenum disulfide nanosheets increases the light absorption and catalytic ability of the aerogel, while making the surface of the aerogel rough, providing more sites for the growth of copper ferrocyanide and an effective place for the photo-Fenton reaction of the catalyst and hydrogen peroxide. Finally, the copper ferrocyanide grown on the surface of the aerogel acts as a catalyst in the photo-Fenton system, achieving the efficient degradation of semi-volatile organic pollutants while the water sample evaporates rapidly on the surface of the photothermal aerogel.
[0023] (2) The firm growth of copper ferrocyanide on the surface of aerogel solves the problems of small powder particle size, easy aggregation in water, and difficulty in recycling in practical applications. More importantly, the introduction of molybdenum disulfide and the loading of copper ferrocyanide greatly enhance the photothermal conversion capacity of aerogel, providing sufficient heat source for solar interfacial evaporation.
[0024] (3) Copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel has excellent photothermal conversion ability. The interfacial evaporation rate of the composite aerogel under three standard solar intensities is 4.48 kg / m 2 h, the light-to-steam conversion efficiency was 87.11%, and the degradation rate of nitrobenzene reached 90.09%. While achieving efficient interface evaporation, the cleanliness of condensed water was effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM photo of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
[0026] Figure 2XRD spectra of graphene oxide, molybdenum disulfide / graphene oxide and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels.
[0027] Figure 3 FT-IR spectra of graphene oxide, molybdenum disulfide / graphene oxide and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels.
[0028] Figure 4 UV-vis curves of graphene oxide, molybdenum disulfide / graphene oxide and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels.
[0029] Figure 5 This is a graph showing the evaporation efficiency of deionized water for graphene oxide, molybdenum disulfide / graphene oxide, and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels under irradiation with different light intensities.
[0030] Figure 6 This is the effect of the amount of hydrogen peroxide added in the solution to be evaporated on the degradation rate of nitrobenzene.
[0031] Figure 7 This is the effect of sodium chloride concentration in the solution to be evaporated on the degradation rate of nitrobenzene. DETAILED DESCRIPTION
[0032] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, a preparation method and application method of a copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel proposed in the present invention, its specific implementation method, characteristics and effects are described in detail as follows. Example 1
[0033] The preparation method of the photothermal aerogel provided in this embodiment is specifically performed as follows: S1. Add 23 mL of concentrated sulfuric acid to a beaker and keep the beaker in an ice bath to cool. Then, add 0.5 g of graphite powder, 0.5 g of sodium nitrate and 3.0 g of potassium permanganate in sequence under mechanical stirring, and continue stirring for 1 h. Place the beaker in an oil bath at 35°C and stir at a constant temperature for 2 h. Then increase the oil bath temperature to 90°C and slowly add 45 mL of deionized water, and continue stirring for 0.5 h. Finally, add 80 mL of deionized water and 2 mL of hydrogen peroxide solution (20 wt%) to the beaker, stir to mix thoroughly, the reaction stops immediately, and the mixture becomes bright yellow. Wash the product 3 times with dilute hydrochloric acid (5 wt%), and wash it several times with deionized water until the pH value reaches neutral. Disperse the obtained product in 50 mL of ultrapure water and ultrasonically treat for 2 h to obtain a graphene oxide dispersion; S2, take 2.498 g of ammonium molybdate tetrahydrate and 4.606 g of thiourea and dissolve them in 60 mL of deionized water, and stir vigorously. Then transfer the mixed solution to a hydrothermal reactor and heat it to 200 ° C. The reaction time is 24 h. After the reaction is completed, it is naturally cooled to room temperature. The black product is rinsed with deionized water and ethanol three times each, and freeze-dried at -50 ° C for 48 h to obtain molybdenum disulfide nanosheets; S3, take 8 mL of graphene oxide dispersion (concentration of 4 mg / mL) and 10 mL of molybdenum disulfide nanosheet dispersion (concentration of 1 mg / mL), mix and ultrasonicate for 1 h, add 3 mL of hydrogen peroxide and 1 mL of polyacrylic acid aqueous solution (concentration of 1 mg / mL), transfer to a high-temperature hydrothermal autoclave, heat to 180°C, react for 8 h, wait for the reaction to be completed, freeze-dry the product at -50°C for 72 h to obtain molybdenum disulfide / graphene oxide aerogel; S4. The molybdenum disulfide / graphene oxide aerogel was placed in 50 mL of copper chloride solution (concentration of 0.1 mol / L) and oscillated for 2 h (speed of 100 rpm), then transferred to 50 mL of potassium ferrocyanide solution (concentration of 0.1 mol / L) and oscillated for 4 h (speed of 130 rpm). The molybdenum disulfide / graphene oxide aerogel modified by copper ferrocyanide was washed with deionized water to remove residual impurities and freeze-dried. The growth process of copper ferrocyanide was repeated 3 times, and the product was freeze-dried at -50 ° C for 72 h to obtain copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
[0034] The application method is as follows: The interface evaporation condensation collection device refers to CN116623421A. A nitrobenzene solution with a concentration of 10 mg / L and 200 mL was added to the beaker, and 0.05 mol / L of hydrogen peroxide was added to the solution. A copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel with a radius of 1.5 cm and a height of 0.8 cm was floated on the liquid surface, and the aerogel was sealed with PE foam. Subsequently, the beaker was placed on an electronic balance and then placed under a solar simulator. The light intensity on the aerogel surface was adjusted to 3 standard solar intensities, and the real-time changes in the amount of water were recorded. The condensed water was collected using a condensation device, and the nitrobenzene concentration in the condensed water was detected. During the solution evaporation experiment, the laboratory temperature was maintained at 25±1°C and the relative humidity was maintained at 50±10%.
[0035] The calculated solar interfacial evaporation rate of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel is 3.84 kg / m 2 h, the light-to-gas conversion efficiency was 77.69%, and the degradation rate of nitrobenzene reached 86.60%. While achieving efficient interfacial evaporation, semi-volatile organic pollutants were effectively degraded. Example 2
[0036] Preparation method and application method of copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel The preparation method of the photothermal aerogel provided in this embodiment is specifically performed as follows: The preparation method of molybdenum disulfide / graphene oxide aerogel is the same as that of Example 1. The molybdenum disulfide / graphene oxide aerogel is placed in 50 mL of copper chloride solution (concentration of 0.2 mol / L) and oscillated for 2 h (speed of 100 rpm), then transferred to 50 mL of potassium ferrocyanide solution (concentration of 0.2 mol / L) and oscillated for 4 h (speed of 130 rpm), and the molybdenum disulfide / graphene oxide aerogel modified by copper ferrocyanide is washed with deionized water to remove residual impurities. The growth process of copper ferrocyanide is repeated 3 times, and the product is freeze-dried at -50°C for 72 h to obtain copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
[0037] The application method is the same as in Example 1. The calculated solar interface evaporation rate of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel is 4.19 kg / m 2 h, the light-to-gas conversion efficiency was 82.53%, and the degradation rate of nitrobenzene reached 89.05%. While achieving efficient interfacial evaporation, semi-volatile organic pollutants were effectively degraded. Example 3
[0038] Preparation method and application method of copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel The preparation method of the photothermal aerogel provided in this embodiment is specifically performed as follows: The preparation method of molybdenum disulfide / graphene oxide aerogel is the same as that of Example 1. The molybdenum disulfide / graphene oxide aerogel is placed in 50 mL of copper chloride solution (concentration of 0.3 mol / L) and shaken for 2 h (speed of 100 rpm), then transferred to 50 mL of potassium ferrocyanide solution (concentration of 0.3 mol / L) and shaken for 4 h (speed of 130 rpm), and the molybdenum disulfide / graphene oxide aerogel modified by copper ferrocyanide is washed with deionized water to remove residual impurities. The growth process of copper ferrocyanide is repeated 3 times, and the product is freeze-dried at -50°C for 72 h to obtain copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
[0039] The application method is the same as in Example 1. The calculated solar interface evaporation rate of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel is 4.48 kg / m 2 h, the light-to-gas conversion efficiency was 87.11%, and the degradation rate of nitrobenzene reached 90.09%. While achieving efficient interfacial evaporation, semi-volatile organic pollutants were effectively degraded. Example 4
[0040] Preparation method and application method of copper ferrocyanide / molybdenum disulfide / graphene oxide photothermal aerogel The preparation method of the photothermal aerogel provided in this embodiment is specifically performed as follows: The preparation method of molybdenum disulfide / graphene oxide aerogel is the same as that of Example 1. The molybdenum disulfide / graphene oxide aerogel is placed in 50 mL of copper chloride solution (concentration of 0.5 mol / L) and oscillated for 2 h (speed of 100 rpm), then transferred to 50 mL of potassium ferrocyanide solution (concentration of 0.5 mol / L) and oscillated for 4 h (speed of 130 rpm), and the molybdenum disulfide / graphene oxide aerogel modified by copper ferrocyanide is washed with deionized water to remove residual impurities. The growth process of copper ferrocyanide is repeated 3 times, and the product is freeze-dried at -50°C for 72 h to obtain copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
[0041] The application method is the same as in Example 1. The calculated solar interface evaporation rate of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel is 4.47 kg / m 2 h, the light-to-gas conversion efficiency was 86.89%, and the degradation rate of nitrobenzene reached 90.05%. While achieving efficient interfacial evaporation, semi-volatile organic pollutants were effectively degraded.
[0042] According to the above experimental results, when the copper ion concentration is in the range of 0.1~0.3mol / L, with the increase of copper ferrocyanide (Cu3[Fe(CN)6]2) content, the solar interface evaporation rate, light-to-vapor conversion efficiency and pollutant degradation rate of the aerogel are improved. This shows that the introduction of copper ferrocyanide enhances the light absorption and light-to-heat conversion capabilities of the aerogel. However, a higher concentration of copper ferrocyanide may lead to aggregation between particles, forming an uneven microstructure, thereby reducing the light absorption efficiency. Comparative Example 1
[0043] The preparation method of graphene oxide aerogel is specifically performed as follows: S1. Obtain a graphene oxide dispersion by referring to the method of Example 1; S2. Take 8 mL of graphene oxide dispersion (concentration of 4 mg / mL), add 3 mL of hydrogen peroxide and 1 mL of polyacrylic acid aqueous solution (concentration of 1 mg / mL), and transfer to a high-temperature hydrothermal autoclave. Heat the temperature to 180°C for 8 h. After the reaction is completed, freeze-dry the product at -50°C for 72 h to obtain graphene oxide aerogel. Comparative Example 2
[0044] Molybdenum disulfide / graphene oxide aerogel was prepared according to the method of Example 1.
[0045] Taking the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel prepared in Example 1 as an example, the material characterization and performance test are as follows: Figure 1 This is a SEM photo of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel. As can be seen from the figure, copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel exhibits a three-dimensional framework microstructure, with a more obvious lamellar structure and a rough surface. The molybdenum disulfide nanosheets on the surface of graphene oxide aerogel enrich the surface morphology, provide more sites for the growth of copper ferrocyanide, increase the light absorption capacity, and also provide a place for the effective reaction of catalyst and hydrogen peroxide. In addition, copper ferrocyanide particles grow uniformly on the surface of molybdenum disulfide / graphene oxide aerogel.
[0046] Figure 2 The XRD spectra of graphene oxide, molybdenum disulfide / graphene oxide and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels are shown in Figure 1. As can be seen from the figure, the peak of graphene oxide aerogel at 2θ=10° is sharp, which is an obvious characteristic peak of the (001) plane. Molybdenum disulfide / graphene oxide aerogel has four diffraction peaks at 13.9°, 33.2°, 39.4°, and 58.6°, which are (002), (100), (103) and (110) crystal planes, respectively, which basically maintain the layered crystallization and diffraction peak position of molybdenum disulfide. This phenomenon indicates that molybdenum disulfide has been successfully combined with graphene oxide. In contrast, the diffraction peak of graphene oxide is difficult to detect, which indicates that the aggregation degree of graphene oxide in the composite aerogel is relatively low. The six new characteristic peaks of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel at 2θ=17.8°, 25.2°, 36.0°, 40.4°, 44.3°, and 51.7° correspond to the 200, 220, 400, 420, 424, and 440 diffraction planes, which are consistent with the standard pattern of copper ferrocyanide (JCPDS card no. 02-0381), indicating that copper ferrocyanide has been successfully grown on the surface of molybdenum disulfide / graphene oxide.
[0047] Figure 3 FT-IR spectra of graphene oxide, MoS2 / graphene oxide, and CuFe2C4 / MoS2 / graphene oxide aerogels. -1 There is a broader and stronger absorption peak near 1730 cm, which is attributed to the stretching vibration peak of OH; -1 The C=O stretching vibration peak on the carboxyl group of graphene oxide is at 1114 cm -1The absorption peak at 878 cm is the COC vibration absorption peak. This indicates that the surface of graphene oxide aerogel contains abundant oxygen-containing functional groups such as hydroxyl, carboxyl and epoxy groups. -1 and 618 cm -1 The bands at 2102 cm-1 belong to the stretching vibrations of Mo-O and Mo-S, confirming the successful combination of graphene oxide and MoS2 in the aerogel. -1 and 593 cm -1 The absorption peaks at correspond to the stretching vibration of C≡N and Fe Ⅱ -C≡N bending vibration, 477 cm -1 C≡N-Cu Ⅱ absorption peak.
[0048] Figure 4 The UV-vis curves of graphene oxide, molybdenum disulfide / graphene oxide and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels. Since graphene oxide and molybdenum disulfide / graphene oxide are black aerogels, they are close to smooth straight lines in the UV-vis spectrum and can absorb the entire band. The molybdenum disulfide / graphene oxide aerogel introduced with molybdenum disulfide has a higher visible light absorption intensity and exhibits a more excellent visible light response ability. Due to the growth of dark red copper ferrocyanide on the surface, the visible light absorption intensity of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel is slightly lower than that of molybdenum disulfide / graphene oxide aerogel, but it still exhibits good visible light absorption ability in the range of 300~800 nm.
[0049] Figure 5 The evaporation efficiency of deionized water for graphene oxide, molybdenum disulfide / graphene oxide, and copper ferrocyanide / molybdenum disulfide / graphene oxide aerogels under different light intensities is shown in Figure 3. In the three solar interfacial distillation systems, the water evaporation rate increases almost linearly with the increase of solar light intensity.
[0050] Figure 6The effect of the amount of hydrogen peroxide added to the solution to be evaporated on the degradation rate of nitrobenzene. In the system without adding hydrogen peroxide, the degradation rate of nitrobenzene is very low. After adding 0.02, 0.05, and 0.08 mol / L of hydrogen peroxide, the degradation rate of nitrobenzene increases linearly. After increasing the content of hydrogen peroxide again, the degradation rate of nitrobenzene remains basically unchanged or even shows a downward trend. This may be that when the content of hydrogen peroxide is moderate, sufficient hydroxyl radicals can be efficiently generated, thereby quickly oxidizing and degrading pollutants to achieve good treatment effects. Excessive hydrogen peroxide may react with hydroxyl radicals to generate water and oxygen, thereby reducing the concentration of hydroxyl radicals, slowing down the degradation rate of pollutants, and the overall efficiency of the reaction will not continue to increase. Therefore, too low a hydrogen peroxide concentration will lead to a decrease in reaction efficiency; when it is too high, the generated hydroxyl radicals will be reacted by hydrogen peroxide, thereby slowing down the oxidation of pollutants.
[0051] Figure 7 The effect of sodium chloride concentration in the solution to be steamed on the degradation rate of nitrobenzene. With the increase of salinity, the efficiency of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel in degrading nitrobenzene gradually decreases. This is because the concentration of ions in the solution increases with the increase of solution salinity, which may increase the probability of hydroxyl radicals being captured by ions, resulting in a decrease in the number of hydroxyl radicals used to oxidize pollutants; in addition, chloride ions in the solution may compete with pollutants for hydroxyl radicals, which will also affect the degradation efficiency of pollutants. In addition, high-salinity solutions may increase the absorption of light by the solution and reduce the light intensity reaching the reaction zone, thereby affecting the excitation efficiency of the light-Fenton reaction and further affecting the amount of hydroxyl radicals generated. Therefore, the increase in salinity in the solution will inhibit the process of copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel in degrading nitrobenzene.
[0052] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been shown as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel, characterized in that: The copper ferrocyanide grows on the surface of molybdenum disulfide / graphene oxide aerogel; the aerogel material is polyacrylic acid, and the mass ratio of graphene oxide to molybdenum disulfide is 3-4:
1.
2. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 1, characterized in that: The steps are as follows: S1, mixing a graphene oxide dispersion and a molybdenum disulfide dispersion, ultrasonically treating the mixture, adding hydrogen peroxide and a polyacrylic acid aqueous solution, and then hydrothermally reacting the mixture, and after the reaction is completed, freeze-drying the product to obtain a molybdenum disulfide / graphene oxide aerogel; S2. The molybdenum disulfide / graphene oxide aerogel was placed in a cupric chloride solution for reaction for 2 h, and then transferred to a potassium ferrocyanide solution for reaction for 4 h, washed, and freeze-dried to obtain copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel.
3. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 2, characterized in that: The concentration of the graphene oxide dispersion described in step S1 is 4-5 mg / mL; the concentration of the molybdenum disulfide dispersion is 1-2 mg / mL; the mass fraction of the hydrogen peroxide solution is 20%-30%; and the concentration of the polyacrylic acid aqueous solution is 1-2 mg / mL.
4. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 3, characterized in that: The volume ratio of the graphene oxide dispersion, the molybdenum disulfide dispersion, the hydrogen peroxide solution and the polyacrylic acid aqueous solution is 8-10:10-12:3-5:1-2.
5. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 2, characterized in that: The graphene oxide dispersion is synthesized by a modified Hummers method, and the specific operation is as follows: under ice bath conditions, 98% concentrated sulfuric acid, graphite powder, sodium nitrate and potassium permanganate are stirred for 1 to 2 hours, and the temperature is raised to 35 to 40 ° C and the stirring is continued for 1 to 2 hours; the temperature is then raised to 90 ° C, and deionized water is slowly added at 1.8 to 2 times the volume of concentrated sulfuric acid, and the stirring is continued for 0.5 to 1 hour; deionized water and hydrogen peroxide are added to terminate the reaction, and the mixture is washed to neutrality, and the concentration of graphene oxide is adjusted with deionized water, and the mixture is evenly dispersed to obtain a graphene oxide dispersion. Among them, the ratio of graphite powder, sodium nitrate and potassium permanganate to concentrated sulfuric acid is: 0.5 to 1.0 g: 0.5 to 1.0 g: 3.0 to 6.0 g: 20 to 25 mL.
6. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 2, characterized in that: The preparation method of molybdenum disulfide is as follows: ammonium molybdate tetrahydrate and thiourea are dissolved in deionized water, stirred evenly, reacted at 200-230° C. for 24 h, cooled to room temperature after the reaction, washed, and dried to obtain molybdenum disulfide nanosheets.
7. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step S1 is 180-200°C, the reaction time is 8 h, and the freeze-drying temperature is -50--60°C, and the time is 48-72 h.
8. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 2, characterized in that: Step S2 also includes repeating the process multiple times to obtain copper ferrocyanide-modified molybdenum disulfide / graphene oxide aerogel.
9. The method for preparing the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 2, characterized in that: In step S2, the concentration of the cupric chloride solution is 0.03-0.5 mol / L, and the concentration of the potassium ferrocyanide solution is 0.03-0.5 mol / L; and / or, the freeze-drying temperature is -50°C, and the time is 72 h.
10. Use of the copper ferrocyanide / molybdenum disulfide / graphene oxide aerogel according to claim 1 in seawater desalination by solar-driven interfacial evaporation and purification of semi-volatile organic wastewater.
Citation Information
Patent Citations
Preparation method and application method of photo-thermal fiber membrane for removing semi-volatile organic compounds in water
CN116623421A